2015
DOI: 10.1007/s10120-015-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear PRMT1 expression is associated with poor prognosis and chemosensitivity in gastric cancer patients

Abstract: Background Metastatic and refractory gastric cancer (GC) are associated with a poor prognosis; therefore, the identification of prognostic factors and chemosensitivity markers is extremely important. Protein arginine methyltransferase 1 (PRMT1) may play a role in chemosensitivity/apoptosis induction via activation of the tumor suppressor forkhead box O1 (FOXO1). The purpose of this study was to clarify the expression of and relationship between PRMT1 and FOXO1 to evaluate the applicability of PRMT1 as a progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…Similarly, YAP is also elevated in various cancers, and emerges as an oncoprotein increasingly being recognized as a promising therapeutic target . Previous studies had documented that overexpression of PRMT1 led to the progression and metastasis of various cancers and predicted a worse prognosis in tumor patients . In addition, nuclear YAP accumulation was independently predictive of poor prognosis in .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, YAP is also elevated in various cancers, and emerges as an oncoprotein increasingly being recognized as a promising therapeutic target . Previous studies had documented that overexpression of PRMT1 led to the progression and metastasis of various cancers and predicted a worse prognosis in tumor patients . In addition, nuclear YAP accumulation was independently predictive of poor prognosis in .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that PRMT1 and YAP can be predictive for the prognosis of patients with several solid tumors, [10][11][12]24,25 thus we had conducted the Kaplan-Meier analysis, and showed that the overall survival rate of patients with high PRMT1 level and YAP-positive tumors was significantly lower than that of patients with low PRMT1 level and YAP-negative tumors, respectively (P = .001; Figure 1G and 1H). Moreover, the combination of PRMT1 level and YAP accumulation had a significant impact on the overall survival (P = .001; Figure 1I).…”
Section: Overexpression Of Prmt1 and Yap Was Associated With High-gmentioning
confidence: 93%
See 3 more Smart Citations